Cover Picture: Elucidating the Doping Effect on the Electronic Structure of Thiolate‐Protected Silver Superatoms by Photoelectron Spectroscopy (Angew. Chem. Int. Ed. 34/2019). Issue 34 (11th July 2019) - Kim, Kuenhee; Hirata, Keisuke; Nakamura, Katsunosuke; Kitazawa, Hirokazu; Hayashi, Shun; Koyasu, Kiichirou; Tsukuda, Tatsuya
Abstract : Doping with heteroatoms is a promising strategy to tune and improve the properties of thiolate‐protected silver superatoms. By using gas‐phase photoelectron spectroscopy, T. Tsukuda and co‐workers reveal in their Communication on page 11637 that substitution of the central X + cation in [XAg24 (SR)18 ] − (X=Ag, Au) by a neutral Pd or Pt atom leads to an energy shift of the superatomic 1P orbitals by about 1.4 eV.